2003
DOI: 10.1038/sj.npp.1300347
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Fluoxetine Treatment Partly Attenuates the Long-Term Anxiety and Depressive Symptoms Induced by MDMA (‘Ecstasy’) in Rats

Abstract: Use of the drug 3,4-methylenedioxymethamphetamine (MDMA, 'Ecstasy') can have long-term adverse effects on emotion in both humans and laboratory animals. The present study examined whether chronic treatment with the antidepressant drug fluoxetine could reverse such effects. Male Wistar rats were briefly exposed to MDMA (4 Â 5 mg/kg over 4 h) or vehicle on 2 consecutive days. Approximately 9-12 weeks later, half of the rats received a dose of approximately 6 mg/kg/day fluoxetine in their drinking water for a 5-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 54 publications
7
42
0
1
Order By: Relevance
“…First, although the assessments of cognitive function and some measures of anxiety-like behavior were similar to those employed by McGregor's group (eg Gurtman et al, 2002;McGregor et al, 2003a, b;Thompson et al, 2004), the profile of MDMA-induced functional alterations was not identical. These discrepancies in outcome are likely due to a combination of factors, including differences in MDMA dosing regimen, rat strain, and possibly the intervals between drug administration and behavioral tests.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…First, although the assessments of cognitive function and some measures of anxiety-like behavior were similar to those employed by McGregor's group (eg Gurtman et al, 2002;McGregor et al, 2003a, b;Thompson et al, 2004), the profile of MDMA-induced functional alterations was not identical. These discrepancies in outcome are likely due to a combination of factors, including differences in MDMA dosing regimen, rat strain, and possibly the intervals between drug administration and behavioral tests.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, Aguirre et al (1998) demonstrated that fluoxetine pretreatment prevented MDMA-induced enhancement of the hypothermic response to a subsequent challenge with 8-hydroxy-2-(di-n-propylamino)tetralin. Moreover, a recent study by Thompson et al (2004) found that chronic fluoxetine treatment following a neurotoxic dosing regimen of MDMA ameliorated many (though not all) of the behavioral changes observed in the MDMAtreated rats. In conjunction with the present results, these findings are consistent with the view that at least some of the short-and long-term functional consequences of MDMA administration are indeed mediated by altered serotonergic activity.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In rodents, a serotonin-selective drug inhibits MDMA-induced effects on the immune system and partly attenuates anxiety and depressive-like behaviors (Pacifici et al 2004;Thompson et al 2004). In human users, the serotonin-selective transport inhibitor citalopram reportedly attenuates the acute psychological (heightened mood, increased self-confidence, and enhanced sensory perception) effects of MDMA (Liechti et al 2000).…”
Section: Discussionmentioning
confidence: 99%